Behind the screen: Unraveling the role of perceived closeness difference in shaping viewers’ engagement behaviors - Runhua Huang; Huichao Guo (PLoS ONE, 2026)
Viewer engagement is central to the live-streaming economy. While existing literature primarily examines the dyadic relationship between a viewer and a streamer, it largely overlooks the social context: viewers simultaneously witness the streamer’s real-time interactions with peers. Drawing on Leader-Member Exchange (LMX) differentiation and Social Comparison Theory, we introduce Perceived Closeness Difference (PCD), defined as the cognitive gap between a viewer’s perceived closeness to the streamer and their perception of a peer’s closeness. Across six experimental studies ( N = 1,980), we examine how PCD is associated with engagement behaviors. Study 1 shows that witnessing a streamer favor a peer (Negative PCD) is associated with lower engagement, whereas witnessing peer rejection (Positive PCD) is associated with higher engagement, partly mediated by participants’ subjectively measured PCD scores. Studies 2 and 3 identify boundary conditions, indicating that these effects are stronger in emotional (vs. utility) contexts and among more emotionally oriented viewers. Study 4 shows that the pattern varies with the peer’s group identity (in-group vs. out-group). Study 5 indicates that PCD is more strongly related to public/social engagement (e.g., commenting) than to private/financial engagement. Finally, Study 6 links PCD to long-term loyalty via perceived streamer trustworthiness. Together, these findings extend one-and-a-half-sided relationship perspectives and offer implications for community management in interactive media.